Interplay between Rapid Diagnostic Tests and Antimicrobial Stewardship Programs among Patients with Bloodstream and Other Severe Infections. (23rd October 2019) - Beganovic, Maya; McCreary, Erin K; Mahoney, Monica V; Dionne, Brandon; Green, Daniel A; Timbrook, Tristan T
Abstract: Background: Antimicrobial stewardship programs (ASPs) aim to provide optimal antimicrobial therapy to patients quickly to improve the likelihood of overcoming infection while reducing the risk of adverse effects. Rapid diagnostic tests (RDTs) for infectious diseases have become an integral tool for ASPs to achieve these aims. Content: This review explored the demonstrated clinical value of longer-standing technologies and implications of newer RDTs from an antimicrobial stewardship perspective. Based on available literature, the focus was on the use of RDTs in bloodstream infections (BSIs), particularly those that perform organism identification and genotypic resistance detection, phenotypic susceptibility testing, and direct specimen testing. Clinical implications of rapid testing among respiratory, central nervous system, and gastrointestinal infections are also reviewed. Summary: Coupling RDTs with ASPs facilitates the appropriate and timely use of test results, translating into improved patient outcomes through optimization of antimicrobial use. These benefits are best demonstrated in the use of RDT in BSIs. Rapid phenotypic susceptibility testing offers the potential for early pharmacokinetic/pharmacodynamic optimization, and direct specimen testing on blood may allow ASPs to initiate appropriate therapy and/or tailor empiric therapy even sooner than other RDTs. RDTs for respiratory, central nervous system, and gastrointestinal illnesses have also shown significant promise, although more outcome studies are needed to evaluate their full impact.